Development of bone scaffold using Puntius conchonius fish scale derived hydroxyapatite: Physico-mechanical and bioactivity evaluations. Issue 8 (1st June 2019) - Deb, Payel; Barua, Emon; Deoghare, Ashish B.; Lala, Sumit Das
Abstract: Naturally derived Hydroxyapatite (HAp) from fish scale is finding wide applications in the development of bone scaffold to promote bone regeneration. But porous HAp scaffold is fragile in nature making it unsuitable for bone repair or replacement applications. Thus, it is essential to improve the mechanical property of HAp scaffolds while retaining the interconnected porous structure for tissue ingrowth in vivo . In this study solvent casting particulate leaching technique is used to develop novel Puntius conchonius fish scale derived HAp bone scaffold by varying the wt.% of the HAp from 60 to 80% in PMMA matrix. Physico-chemical, mechanical, structural and bioactive properties of the developed scaffolds are investigated. The obtained results indicate that HAp-PMMA scaffold at 70 wt % HAp loading shows optimal properties with 7.26 ± 0.45 MPa compressive strength, 75 ± 0.8% porosity, 8.0 ± 0.68% degradation and 190 ± 11% water absorption. The obtained results of the scaffold can meet the physiological demands to guide bone regeneration. Moreover, in vitro bioactivity analysis also confirms the formation of bone like apatite in the scaffold surface after 28 days of SBF immersion. Thus, the developed scaffold has the potential to be effectively used in bone tissue engineering applications.